2013
DOI: 10.1128/jvi.03278-12
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Genomics of Human Respiratory Syncytial Virus Subgroups A and B: Genetic Variability and Molecular Evolutionary Dynamics

Abstract: Genomic variation and related evolutionary dynamics of human respiratory syncytial virus (RSV), a common causative agent of severe lower respiratory tract infections, may affect its transmission behavior. RSV evolutionary patterns are likely to be influenced by a precarious interplay between selection favoring variants with higher replicative fitness and variants that evade host immune responses. Studying RSV genetic variation can reveal both the genes and the individual codons within these genes that are most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 78 publications
15
79
0
Order By: Relevance
“…The higher genetic variability of group A strains may partially account for their more frequent global appearance due to their greater genetic plasticity (Coggins et al, 1998), although the overall ratio of dN/dS suggests that the majority of substitutions are neutral. Therefore, the high variability found in the G gene is not entirely driven by host immunity evasion (Tan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The higher genetic variability of group A strains may partially account for their more frequent global appearance due to their greater genetic plasticity (Coggins et al, 1998), although the overall ratio of dN/dS suggests that the majority of substitutions are neutral. Therefore, the high variability found in the G gene is not entirely driven by host immunity evasion (Tan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic differences between the two subgroups of HRSV are predominantly mediated by the highly variable G gene (10) and might facilitate evasion of host immune responses (43). Despite these differences, infections with HRSV of either subgroup cause indistinguishable disease (1).…”
Section: Discussionmentioning
confidence: 99%
“…The glyco-(G) proteins facilitate virus attachment and entry (1,7), and the F glycoprotein is an important target of virus neutralizing antibodies (8). Molecular epidemiological studies have identified two HRSV subgroups (A and B), which cause indistinguishable disease and cocirculate during, or alternate between, yearly outbreaks (9,10).…”
mentioning
confidence: 99%
“…Of these envelope glycoproteins, only the RSV F protein is indispensable for viral replication in vitro (9). It is the most conserved RSV glycoprotein and also the main target of neutralizing antibodies and vaccine development (10,11). Initially, the RSV F protein assembles into a homotrimeric, metastable prefusion conformation that rearranges to a highly stable postfusion conformation during fusion of the viral and target cell membrane or spontaneously (12).…”
mentioning
confidence: 99%